On the determinants of pro-environmental behavior: A guide for further investigations - Ann-Kathrin Blankenberg; Harm Alhusen (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
Determinants of pro-environmental behavior (PEB) have been studied rigorously in the past decades. Given this spurt, a systematic review of extant research is required to determine factors involved, analyze impact and identify research gaps and new directions. This paper provides a systematic review of current economic and psychological studies regarding the determinants of PEB. As a result, we show that PEB is determined by an interplay of socioeconomic, psychological and further (individual, social, institutional) factors, which need to be considered in its study. In addition, PEB needs to be analyzed with multiple items rather than by focusing on single ones as the impact of the determinants differs depending on the analyzed behavior. To express it in economic terms, the coefficient of each determinant can either be positive or negative, given the specific type of analyzed behavior (low vs high cost behavior). By combining the results from economics and psychology, this work offers a starting point for a more sophisticated understanding of PEB.
Is replaced by the following version: http://hdl.handle.net/10419/204821
Keywords: 330; determinants of pro-environmental behavior; ecological economics; review